Adsorbent effectiveness of α-cellulose/humatic acid with epichlorohydrin cross-linking agent on methyl orange dye - Asri Widyayanti, Oksita; Mohtar, Cici Farhana Ambarwanty; Jaman, Anwar (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Adsorption of methyl orange (MO) using epichlorohydrin cross-linked humic acid/cellulose composite has been carried out. This study aims to synthesize epichlorohydrin cross-linked humic acid/cellulose composites, determine the optimum pH, contact time, and initial concentration and study MO desorption. The adsorbent production begins with the isolation of cellulose from empty palm oil bunches (EFB) obtained from North Sumatra and the isolation of humic acid from peat soil obtained from Rawa Pening. Then humic acid was cross-linked to cellulose in an alkaline solution (NaOH), then epichlorohydrin was added as a cross-linking agent while heating at 600C for 2 hours. Epichlorohydrin cross-linked humic acid/cellulose adsorbents (AH/Cell-ECH) were further characterized using FTIR, XRD and SEM spectroscopy. MO solutions before and after adsorption were analyzed using UV-Vis spectrophotometry. MO desorption studies used HCl pH 4, 0.1 and 1.0 M NaCl and 40% and 60% ethanol. FTIR characterization showed that the AH/Sel-ECH adsorbents had active groups, including –OH, -C=O, and –COOH. Characterization using XRD showed diffraction peaks in the 2θ region around 11.41, 20.25, 22.55, and 42.66o, indicating the presence of galactose, xylose, glucose and polysaccharide phases. The SEM-EDX results showed that the surface of the adsorbent had non-uniform pore sizes, and the surface morphology tended to be clean and free of debris. It indicated the presence of C, O, and N elements in AH/ECH-cells and S, N elements after MO adsorption. The optimum interaction of AH/Sel-ECH with MO occurred at pH 2 with 150 mg/L MO, and a contact time of 120 minutes was obtained. MO adsorption by AH/ECH-cells followed a pseudo-second-order kinetics model and the Freundlich isotherm with an MO adsorption capacity of 9.84 x 10-5 mmol/g, respectively. Desorption studies showed that 60% ethanol was the most effective solution for desorption of MO.